DIE SPRICHWÖRTER UND EPIGRAMME DES ULGERIUS VON ANGERS - Wollin, Carsten (Proverbium - Yearbook, 2012)
Among the Latin Carmina of bishop Ulgerius of Angers (pont. 1125-1148) has been preserved a small group of 17 proverbs and epigrams, some imitating the Roman classics, some translating Old-French proverbs, some referring to contemporary events. The present article provides the first critical edition of these poems, including a German translation and commentary.